Antiaging compounds from marine organisms. (May 2021) - Wang, Xiaomei; Zhang, Zhongshan; Zhang, Shaoyong; Yang, Fan; Yang, Min; Zhou, Junbo; Hu, Zuguang; Xu, Xiaogang; Mao, Genxiang; Chen, Guangming; Xiang, Wenzhou; Sun, Xue; et al.
Graphical abstract: Highlights: The prospective antiaging substance from marine macroalgae, micaroalgae, invertebrate and vertebrate were reviewed. The activity and mechanism of antiaging substance from marine organisms were revealed. The problems and prospects aspects were discussed for future research in this field. Abstract: Marine organisms have received mounting attention in antiaging activity due to their exclusive chemicals. This review aims at revealing and discussing prospective antiaging substance from marine macroalgae, micaroalgae, invertebrate and vertebrate. The activity and mechanism of the carbohydrate, protein, pigment, flavonoids, fatty acids, phenols from marine organisms were revealed through a variety of antiaging experimental models such as rats, Drosophila melanogaster and Caenorhabditis elegans. And meanwhile, the problems and prospects aspects were discussed for future research in this field. It was suggested that the antiaging functional ingredients from these marine organisms are alternative sources for synthetic ingredients that can contribute to consumer's well-being, as part of nutraceuticals, functional foods and cosmetics.